P108 Survival outcomes in patients with high risk LENT malignant pleural effusions managed with indwelling pleural catheter intervention; a specialist centre experience. (12th November 2019) - Hardeep Kalsi, HS; Park, M; Owles, H; Wyndham, S; Ross, C
Abstract : Introduction: Management of malignant pleural disease has advanced over the past decade with the role of a pleural specialist service becoming increasingly essential in efforts to optimise patient care. The use of indwelling pleural catheters (IPC) has changed the arena in which malignant pleural effusions (MPE) can be managed, allowing more patient autonomy and less use of hospital resources. The LENT scoring system, validated in 2014, is often used to guide decision making in patients with MPE. Current ATS recommendations suggest IPCs are not suitable in individuals with a 'very short survival' prognosis however this determination is variable and is an example of where the LENT scoring system may be involved. Methods: Retrospective analysis was carried out on patients who underwent IPC insertion at our institution between 2016 and 2019. All patients were seen in the specialist pleural service and underwent subsequent intervention. Data collected included primary cancer diagnosis, date of first pleural aspiration, LENT score, observed complications, IPC removal date if applicable and date of death to calculate survival time. Results: 58 patients underwent successful IPC insertion of which 5 were for non-malignant disease (2/5 refractory heart failure, 3/5 advanced liver cirrhosis). The remaining 53 patients all had a confirmed pathological diagnosis of malignant pleural effusion. At the time of submission, 8 patients remained alive and were excluded from analysis leaving a remaining 45 cases. Using LENT assessment 13/45 classed as high risk, 31/45 as moderate and 1/45 as low. The observed average survival time in high risk patients was 122 days and median 93 days. This was notably higher than the anticipated 44 days predicted median survival time noted in the literature. Conclusion: Our data suggests that high risk patients according to LENT assessment were more likely to live longer following IPC intervention and aftercare. This suggests that use of prognostic assessment tools may be ineffective in this sub-group and should be employed with caution. The improved patient outcomes reinforce the benefit of a dynamic responsive pleural service. They may also reflect upon the increased recognition of tumour heterogeneity alongside the recent advent of novel molecular based therapies.